Initial Human Exploration at the Southern End of the Deseado Massif? - Franco, Nora Viviana (2012)
Lithic artifacts, in conjunction with other evidences, provide useful information about the way in which humans have explored and occupied the patagonian landscape. According to Borrero (1994-95) exploration implies the initial radiation to new land and implies displacement of individuals or groups following the less resistance natural routes, with repeated, widely separated camping places. As a result new territory can be incorporated. In the long run the process is one of slow expansion of human home ranges. On the other hand, the incorporation of new land implies the operation of variable learning processes (e.g. Rockman 2003). The velocity of incorporation of new land will vary according with the degree of homogeneity between the new and original environment and other factors (see for example Steele and Rockman 2003). This is why the problem of exploration and incorporation of new land should be addressed at a regional or macroregional scale.